The invisible quantity: time intervals in early algebra / La cantidad invisible: los intervalos de tiempo en el álgebra temprana. Issue 3 (3rd July 2019) - Earnest, Darrell
Abstract: A common context for instruction in early algebra involves time, an invisible and intangible quantity commonly represented as intervals of length. This paper presents a case study of syntactically guided reasoning with the structure of an analogue clock involving a second-grade student. As her descriptions shifted from clock-reading procedures to a treatment of interval, she integrated conflicting ideas related to learned procedures for clock reading with time as experienced in the world. I discuss implications for early algebra related to strands for functions and quantitative reasoning.